1999
DOI: 10.3109/01674829909075590
|View full text |Cite
|
Sign up to set email alerts
|

Memory in pregnancy. II: Implicit, incidental, explicit, semantic, short-term, working and prospective memory in primigravid, multigravid and postpartum women

Abstract: This study, using an information processing model of memory, made a detailed examination of the possible locus (loci) of any memory change in gravid and postpartum women using a battery of seven objective memory tests: implicit, incidental, explicit, semantic, short-term, working, and prospective memory. In addition, links were sought both between (a) self-reported data on sleep, health, and memory performance, and (b) these variables and objective memory performance. Five groups of women were tested (n = 22/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
69
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 5 publications
15
69
2
1
Order By: Relevance
“…The cognitive processes associated with the pregnant woman's understanding of her present condition seem to extend to the PG state, producing a biased set of memories 22 . As a result of this fact another consequence arises: answers given in the T2 and T3 might have suffered influences of the experiences related to the sleep pattern of previous trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive processes associated with the pregnant woman's understanding of her present condition seem to extend to the PG state, producing a biased set of memories 22 . As a result of this fact another consequence arises: answers given in the T2 and T3 might have suffered influences of the experiences related to the sleep pattern of previous trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies have asked only for ratings of general memory ability (Brindle et al, 1991;Casey et al, 1999;Christensen et al, 1999;Janes et al, 1999;McDowell and Moriarty, 2000;Sharp et al, 1993). Those that have examined other aspects of cognition Kane et al, 1968;Parsons and Redman, 1991;Poser et al, 1986) have shown that in addition to memory difficulties, some pregnant women also report increased absentmindedness and impairments in concentration, reading ability and clarity of thought.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies in which women rate their cognitive abilities in pregnancy compared with their usual performance show that many perceive a decline during pregnancy (e.g. Brindle et al, 1991;Casey et al, 1999;Christensen et al, 1999;Janes et al, 1999;McDowell and Moriarty, 2000;Parsons and Redman, 1991;Poser et al, 1986;Sharp et al, 1993). Yet it is not clear how salient these changes are in the overall context of the many changes accompanying pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Data from our previous study of implicit memory across the lifespan [30] indicate a slight female advantage on CEG priming (P =0.06) and a significant advantage on conceptual explicit memory (see Appendix A). Conversely, studies of memory during pregnancy lead to the speculation that unusually high levels of sex steroid hormones may detrimentally affect performance on both explicit and implicit memory tests [5,7,23,42]. Pregnancy is characterized by dramatic hormonal fluctuations, including unusually high levels of estrogen, progesterone, oxytocin, and other hormones [15].…”
Section: Introductionmentioning
confidence: 99%
“…word-stem completion). Two studies reported impairments among pregnant women [5,42], and two other studies found no difference between pregnant and nonpregnant women on the test [7,23]. Isolating and understanding the influence of estrogen on memory in pregnancy is difficult because the hormonal milieu is complex and fluctuates throughout pregnancy and the relation between estrogen levels and memory performance may be nonlinear.…”
Section: Introductionmentioning
confidence: 99%